Harapan Dan Kenyataan Berkarier Di Kantor Akuntan Publik: Suatu Perbandingan Antara Mahasiswi Akuntansi Dan Auditor Perempuan - Marita, Dini (Universitas Multimedia Nusantara, 2011)
This research is a kind of comparative research which is conducted to examine the differences of perception between a group of accounting students and women auditors in public accounting firm based on the job duties and responsibilities, advancement, training, and supervision, personal concern, and also financial remuneration. The object of this research are accounting female students from several universities which are located in Jakarta and in surrounding areas, and the women auditors who worked in public accounting firms in Jakarta. The validity of data was analyzed by using Pearson Correlation, the reliability of data was analyzed by using the Cronbach's Alpha coefficient (α), the normality of data was analyzed by using the Kolmogorov-Smirnov, and the hypothesis was analyzed by using the Independent Sample t-Test. The results of hypothesis from the four variables of research showed that there are significant differences of perception between accounting female students and women auditors working in public accounting firm (KAP) concerning about job duties and responsibility, advancement, training and supervision, personal concern, and financial remuneration. Keywords: advancement, financial remuneration , job duties and responsibility, personal concern, supervision, training.